1999
DOI: 10.1152/jappl.1999.86.6.1770
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oral glutamine on whole body carbohydrate storage during recovery from exhaustive exercise

Abstract: The purpose of this study was to determine the efficacy of glutamine in promoting whole body carbohydrate storage and muscle glycogen resynthesis during recovery from exhaustive exercise. Postabsorptive subjects completed a glycogen-depleting exercise protocol, then consumed 330 ml of one of three drinks, 18.5% (wt/vol) glucose polymer solution, 8 g glutamine in 330 ml glucose polymer solution, or 8 g glutamine in 330 ml placebo, and also received a primed constant infusion of [1-13C]glucose for 2 h. Plasma gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0
8

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 28 publications
0
52
0
8
Order By: Relevance
“…Glutamine supplementation managed to prevent a decrease of maximum and minimum power. It has been shown that ingestion of pure glutamine promoted muscle glycogen re-synthesis during recovery from exhaustive exercise [19]. Although the decreases in anaerobic power and field goal percentage did not reach significance, the results suggest that the combination of high intensity, moderate duration exercise, and fluid restriction might be detrimental to performance [20].…”
Section: Resultsmentioning
confidence: 78%
“…Glutamine supplementation managed to prevent a decrease of maximum and minimum power. It has been shown that ingestion of pure glutamine promoted muscle glycogen re-synthesis during recovery from exhaustive exercise [19]. Although the decreases in anaerobic power and field goal percentage did not reach significance, the results suggest that the combination of high intensity, moderate duration exercise, and fluid restriction might be detrimental to performance [20].…”
Section: Resultsmentioning
confidence: 78%
“…Most of these studies have shown short-term effects of glutamine supplementation however, long-term supplementation showed to be a more effective application of glutamine in regards to strength gains. Although glutamine may simulate muscle glycogen synthesis, Varnier et al (1995) and Bowtell et al (1999) demonstrated that infusion and oral glutamine supplementation promotes storage of muscle glycogen. On this basis one current widely used supplement is L-glutamine, which increases protein synthesis within skeletal muscle leading to enhanced muscle growth.…”
Section: Discussionmentioning
confidence: 99%
“…Glutamine is one of the most popular dietary supplements marketed to athletes and physically active individuals (Varnier et al, 1995;Bowtell et al, 1999). Also glutamine is involved in so many physiological processes, it has been suggested that glutamine supplementation may assist athletes by: providing nutritional support for the immune system and preventing infection, improving cellular fluid retention, increasing water absorption from the gut, encouraging muscle glycogen synthesis, stimulating muscle protein synthesis, therefore enhance muscle growth, reducing muscle soreness and enhancing tissue repair and enhancing buffering capacity (Varnier et al, 1995;bowtell et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of enough glutamine the body takes the necessary proteins from the muscles that seem to be aging. Glutamine retards the aging process, so it is often called the ' Inner Fountain of Youth ' [23].…”
Section: Glutamine For Firm Skin and Controls The Acid-base Balance Imentioning
confidence: 99%